Performance, health, bacterial metabolites and intestinal histomorphology in does and growing rabbits fed diets with increasing lignocellulose-to-cellulose proportions. Issue 2 (4th March 2022) - Saliu, Eva-Maria; Krieg, Ronald; Martínez-Vallespín, Beatriz; Simon, Annette; Zentek, Jürgen
ABSTRACT: Adequate levels of dietary fibre can reduce the risk of intestinal health disorders in rabbits after weaning. Therefore, it was the aim of the study to investigate the impact of different lignocellulose and cellulose addition to rabbits' diets on performance and intestinal traits in lactating does and weaned rabbits. A total of 60 rabbit does (4.41 ± 0.45 kg body weight) were fed isonitrogenous diets with lignocellulose and cellulose inclusion rates [%] of 0/8, 2/6, 4/4, 6/2 and 8/0, resulting in dietary lignin-to-cellulose ratios of 0.26, 0.30, 0.32, 0.34 and 0.40, respectively. The diets were fed from 4 d ante partum (a.p.) until day 28 post partum (p.p. weaning). After weaning, 40 young rabbits from each feeding group were fed the same diets for 12 d, when 10 rabbits per group were sacrificed. Body weight gain (BWG), feed intake and feed conversion ratio were obtained. Gastrointestinal content and gut tissue were obtained from the growing rabbits and pH, short-chain fatty acids (SCFA) concentration and gut morphology were investigated. Digestive disorders were scored, and the sanitary risk index was calculated. Does fed the highest lignocellulose addition increased their feed intake [g · kg BW −1 · d −1 ] in the first two weeks p.p. ( p < 0.001) and increased BWG ( p < 0.001) but without impact on their offsprings' performance. Weaned rabbits fed the highest lignocellulose inclusion showed a reduced feed intake and increased sanitary risk index. Additionally, a higher number of rabbits showed intestinal disorders for a short time (1–2 d, p < 0.001). In the colon content, a higher pH and a lower dry matter content were observed in this group. Caecal contents of 40-d old rabbits showed lower total SCFA, acetate and propionate and higher i-valerate and L-lactate concentrations after feeding diets with high lignocellulose contents. The diet did not influence the acetate-to-propionate ratio. No histomorphological changes were observed in the jejunum, while crypt depth and width were reduced in the caecum of weaned rabbits fed diets with lignocellulose addition. It can be concluded that different proportions of lignocellulose to cellulose addition to rabbits' diets have an impact on health and performance with differences between does and weaned rabbits. While a high lignocellulose inclusion proved beneficial for does, for weaned rabbits, a lower addition should be preferred.